A taxonomic revision of the South Asian hump-nosed pit vipers (Squamata: Viperidae: Hypnale) - Maduwage, Kalana; Silva, Anjana; Manamendra-Arachchi, Kelum; Pethiyagoda, Rohan (Zootaxa, 2009)
The hump-nosed pit vipers of the genus Hypnale are of substantial medical importance in Sri Lanka and India, being included among the five snakes most frequently associated with life-threatening envenoming in humans. The genus has hitherto been considered to comprise three species: H. hypnale, common to Sri Lanka and the Western Ghats of peninsular India; and H. nepa and H. walli, both of which are endemic to Sri Lanka. The latter two species have frequently been confused in the literature. Here, through a review of all extant name-bearing types in the genus, supplemented by examination of preserved specimens, we show that H. nepa is restricted to the higher elevations of Sri Lanka’s central mountains; that H. walli is a junior synonym of H. nepa; and that the endemic species widely distributed in the island’s south-western ‘wet-zone’ lowlands is H. zara. We also draw attention to a possibly new species known only from a single specimen collected near Galle in southern Sri Lanka. We illustrate all four species in colour, and provide a key to their identification and maps delineating their distribution.